2018
DOI: 10.3389/fpls.2018.01437
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the Wheat Protein Phosphatase 2A Catalytic Subunit TaPP2Ac Enhances Host Resistance to the Necrotrophic Pathogen Rhizoctonia cerealis

Abstract: Eukaryotic type 2A protein phosphatases (protein phosphatase 2A, PP2A) consist of a scaffold subunit A, a regulatory subunit B, and a catalytic subunit C. Little is known about the roles of PP2Ac proteins that are involved in plant responses to necrotrophic fungal pathogens. Sharp eyespot, caused by the necrotrophic fungus Rhizoctonia cerealis, is a destructive disease of wheat (Triticum aestivum), an important staple food crop. Here, we isolated TaPP2Ac-4D from wheat, which encodes a catalytic subunit of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…For wheat, a PP2A catalytic subunit belonging to family II (TaPP2Ac) negatively regulates the expression of genes for the antioxidant enzymes CAT and APX2 as well of the pathogenesis response protein PR2. Infection with the fungal pathogen Rhizoctonia cerealis increases the expression of this PP2Ac and exogenous H 2 O 2 application resembles this effect [39]. As we will see for pathway 3 [29], changes of PP2Ac activities that are due to misfunctioning of B regulatory subunits have partially different effects in ROS signaling, which underlines that the relevant involvement of this phosphatase depends largely on the type of activity change and subcellular localization of these effects.…”
Section: The Involvement Of Pp2a In Oxidative Stress Pathwaysmentioning
confidence: 97%
“…For wheat, a PP2A catalytic subunit belonging to family II (TaPP2Ac) negatively regulates the expression of genes for the antioxidant enzymes CAT and APX2 as well of the pathogenesis response protein PR2. Infection with the fungal pathogen Rhizoctonia cerealis increases the expression of this PP2Ac and exogenous H 2 O 2 application resembles this effect [39]. As we will see for pathway 3 [29], changes of PP2Ac activities that are due to misfunctioning of B regulatory subunits have partially different effects in ROS signaling, which underlines that the relevant involvement of this phosphatase depends largely on the type of activity change and subcellular localization of these effects.…”
Section: The Involvement Of Pp2a In Oxidative Stress Pathwaysmentioning
confidence: 97%
“…Recently, Zhu et al (2018) demonstrated the importance of PP2A in host-necrotroph interactions in crop species. Silencing of a wheat (Triticum aestivum) PP2A catalytic subunit conferred resistance against the necrotrophic fungus Rhizoctonia cerealis, the causative agent of wheat sharp eyespot disease.…”
mentioning
confidence: 99%
“…Silencing of a wheat (Triticum aestivum) PP2A catalytic subunit conferred resistance against the necrotrophic fungus Rhizoctonia cerealis, the causative agent of wheat sharp eyespot disease. The resistance phenotype was accompanied by increased transcript abundance for the wheat pathogenesis-related (PR) protein PR2 and antioxidant enzymes (Zhu et al, 2018). However, the exact molecular mechanisms by which PP2A contributes to plant resistance against necrotrophic fungal pathogens remain unresolved.…”
mentioning
confidence: 99%
“…The expression of PRs genes up-regulated in the resistance cultivar than in susceptible wheat cultivar upon infection by Bipolaris sorokiniana and T. controversa [ 9 , 31 ]. The silencing or overexpression of TaPR-5 and TaLHY genes decrease or increase the resistance level against plant pathogens [ 30 , 61 , 62 ]. Here in the qRT-PCR analysis results revealed that infection with T. controversa triggers the expression levels of PRs genes ( TaPR-4 and TaPR-5 ) and TaLHY gene more in resistant and moderately resistance cultivars than in the susceptible cultivar.…”
Section: Discussionmentioning
confidence: 99%